The Effectiveness of Communicative Arabic Language Teaching Materials in Light of the Message of Moderate Values - Nuruddin, Ahmad; Sutaman, Sutaman; Ahmad Mubaligh; Syukran Syukran; Muhammad Iqbal Fathoni; Achmad Ja’far Sodik (Universitas Islam Negeri Raden Intan Lampung, 2025)
The lack of Arabic language teaching materials that integrate a communicative approach and moderate values ​​simultaneously. This study aimed to determine the effectiveness of communicative Arabic language teaching materials developed based on moderate values ​​messages on improving students' Arabic language skills. Moderate values ​​such as tolerance (at-tasāmuh), balance (al-tawāzun), and anti-radicalism are integrated into teaching materials in the form of texts, dialogues, and language exercises. A quantitative approach was applied with a quasi-experimental design. The subjects of the study consisted of 57 students, with 27 students in the experimental class and 30 students in the control class at Al-Izzah Batu High School. The research instruments in the form of pretest and posttest tests were used to measure student learning outcomes. Normality and homogeneity tests showed that the data were normally distributed and the variance was homogeneous. The t-test results showed a significance value of 0.000 (<0.05), which means that there was a significant difference between the learning outcomes of students in the experimental and control classes. The N-Gain calculation showed an increase of 65.22%, which is included in the moderate category. These results indicated that the use of communicative teaching materials based on moderate values ​​is effective in improving students' Arabic language skills while instilling moderate character. This study recommended the use of Arabic language teaching materials that are taught not only as a means of communication, but also as a means of internalizing the values ​​of moderation.